Mitigating Estimation Challenges in Large-Scale Projects: An Integrated Framework for Enhanced Accuracy and Adaptability - Somula, Sasidhar Reddy (IPHO-Journal of Advance Research in Science And Engineering, 2025)
Large-scale project estimation presents fundamental challenges that can significantly impact organizational outcomes, resource allocation, and stakeholder confidence. This article examines essential strategies for enhancing estimation accuracy across complex initiatives characterized by technical complexity, interdependence, and evolving requirements. Beginning with stakeholder engagement as a foundation for comprehensive perspective integration, the article progresses through structural decomposition methodologies that transform overwhelming complexity into manageable components. Risk-informed estimation approaches introduce quantitative techniques for uncertainty modeling and contingency allocation, establishing transparent communication about confidence levels while creating structured reserves for variance accommodation. The article culminates with adaptive estimation frameworks that implement systematic recalibration mechanisms throughout the project lifecycle, maintaining alignment between estimation models and emerging implementation realities. Together, these interconnected approaches establish an integrated framework that transforms estimation from deterministic prediction into a continuous process, enhancing forecast reliability while acknowledging the inherent uncertainty of complex initiatives.